Synthesis and Structural Characterization of Diiron Azadithiolate Complex [(μ-SCH2)2NCH2CO2Me]Fe2(CO)4(CN-tert-Bu)2 - Li, Hui; Gong, Qiaojuan; Chai, Xiaochuan; Yao, Chenzhong; Han, Qiuping (Asian Journal of Chemistry, 2015)
A diiron azadithiolate complex [(μ-SCH2)2NCH2CO2Me]Fe2(CO)4(CN-tert-Bu)2 (1), as the active site of [FeFe]-hydrogenases, has been prepared by carbonyl substitution and structurally characterized. The title complex was prepared by reaction of [(μ-SCH2)2NCH2CO2Me]Fe2(CO)6 (A) with tert-BuNC in CH2Cl2 in 46 % yield. The new complex was characterized by IR, 1H NMR and 13C NMR spectroscopy.